Determination of Manganese in Sludge, Alloy, and Soil by Tungsten Coil Atomic Emission Spectrometry - Gonzalez, Mario Henrique [UNESP] (2015)
A tungsten coil atomic emission spectrometer (WCAES) was developed and evaluated for the determination of manganese in industrial sludge, alloy, and soil. The system employed a coil extracted from a 150 watts/15 volts commercial slide projector light bulb and a simple power supply that provided a constant current to the coil. The analytical signals were resolved and detected using a Czerny-Turner spectrometer and a charge coupled device. Three manganese emission lines were detected simultaneously. Using different emission lines, limits of detection for manganese varied from 0.54 to 0.65 milligram per liter, and relative standard deviations for manganese at 5 milligrams per liter varied from 5.9 to 8.5 percent (n = 10). Summation of the Mn signals improved the detection limit to 0.17 milligram per liter and decreased the relative standard deviation to 1.7 percent. Spectral interferences were observed in the presence of Al, Ca, K, and Na. The accuracy was determined using two certified reference materials, and the results obtained by WCAES were in agreement with those obtained by inductively coupled plasma-optical emission spectrometry at the 95 percent confidence level.